Early Diagnosis of Sinusitis Using Expert System Methods: Early Diagnosis of Sinusitis Using Expert System Methods - Agus Iskandar; Agung Triayudi (Jurnal Mantik, 2020)
Sinusitis is a disease of the nose, which occurs due to inflammation of the sinuses due to allergies or infection with viruses, bacteria or fungi. Sinusitis can occur in any of the four sinuses (maxillary, etmoidalis, frontalis, sphenoidalis). The most common causes of sinusitis are due to viral infections. Often times it is caused by a cold or flu virus that is spread by the sinuses from the upper respiratory tract. After a cold or flu, secondary bacterial infection can occur. This will cause the walls of the sins to become inflamed or inflamed. An infected tooth can also make the sinuses infected. A doctor can diagnose sinusitis by looking at the symptoms that occur. For example, nasal congestion or runny nose with facial pain. If the sinusitis is severe or recurs, You are advised to see an ENT specialist (ear, nose, throat). These specialists will try to find the main cause of sinusitis that occurs. CT scans can also be used to find out the cause of sinusitis. Therefore, an expert system application was made using the forward chainy method to diagnose sinusitis. This system application is a system that helps doctors (experts) and the public in diagnosing sinusitis with symptoms felt by users. an expert system application was made using the forward chainy method to diagnose sinusitis. This system application is a system that helps doctors (experts) and the public in diagnosing sinusitis with symptoms felt by users. an expert system application was made using the forward chainy method to diagnose sinusitis. This system application is a system that helps doctors (experts) and the public in diagnosing sinusitis with symptoms felt by users